Needs Analysis of Articulate Storyline 3-based interactive learning media, assisted by Canva for Colloid Topic - Esti Miranda; Muhammad Amir Masruhim; Yuli Hartati (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Concepts in chemistry, such as colloids, remain challenging for students who struggle to grasp them, and current instructional media used by teachers have not optimally visualized these concepts. This study aims to analyze students’ needs for Articulate Storyline 3–based interactive learning media, supported by Canva, for the colloid topic. Employing a descriptive quantitative design, the study sampled one chemistry teacher and 40 twelfth-grade students from SMA IT Granada Samarinda selected through purposive sampling. Data were collected via questionnaires and an unstructured interview with the teacher. The questionnaire’s validity and reliability were evaluated using Pearson’s Product-Moment correlation in IBM SPSS 27, and questionnaire data were analyzed using descriptive percentage statistics. Findings indicate that 84.5% of students have adequate access to digital devices, 83% prefer visually oriented learning media, and 76.5% express a need for interactive learning tools. The proposed interactive media, developed with Articulate Storyline 3 and Canva, are expected to include instructional videos, interactive exercises, and simple educational games aligned with colloid concepts, making learning more engaging and accessible. This study can serve as a foundation for further development of innovative, adaptive interactive learning media.